Multiple Molecular Determinants for Allosteric Modulation of Alternatively Spliced AMPA Receptors - Quirk, Jennifer C. (J Neurosci, 2003)
Positive allosteric regulation of glutamate AMPA receptors involves conformational changes that can attenuate receptor desensitization and enhance ion flux through the channel pore. Many allosteric modulators (e.g., cyclothiazide and aniracetam) preferentially affect the flip (i) or flop (o) alternatively spliced isoform of AMPA receptors, implicating residues in the flip-flop domain as critical determinants of splice variant sensitivity. Indeed, previous mutational analyses have demonstrated that the differential sensitivity to cyclothiazide and aniracetam depends on a single amino acid, Ser (flip) and Asn (flop), suggesting that this residue may be solely responsible for differences in modulation of AMPA receptor isoforms. The present studies tested this hypothesis by investigating the molecular determinants of modulation of AMPA receptor splice variants by a structurally distinct compound, LY404187, which displays strikingly different and opposing kinetics of allosteric regulation characterized by a time-dependent enhancement in potentiation of homomeric GluR1-GluR4i and a time-dependent reduction in potentiation of GluR1-GluR4o. Site-directed mutagenesis of residues in the flip-flop domain of GluR2 revealed that, although exchange of Asn775 for Ser in GluR2o was sufficient to confer the GluR2i phenotype of potentiation, the corresponding mutation, Ser775Asn, in GluR2i did not impart the GluR2o response. In fact, the GluR2o kinetics of modulation depended on a novel set of substitutions in GluR2i, including Thr765Asn, Pro766Ala, and Val779Leu in combination with Ser775Asn. Collectively, these results show that, unlike cyclothiazide and aniracetam, the residues that confer splice variant differences in modulation by LY404187 are not identical and indicate that allosteric regulation of AMPA receptors can arise from multiple molecular determinants.